Synthesis, Structure and Antibacterial Activity of 1, 4-bis (1-benzimidazolyl) butane Complexes with some Transition Metal Salts - Abbas Washeel Salman (Journal of Global Pharma Technology, 2018)
This study presents the synthesis, characterization and antibacterial activity of Mn2+, Co2+, Ni2+, Cu2+, Zn2+ and Ag+ complexes derived from the ligand 1,4-bis(1-benzimidazolyl) butane (Dbz). The ligand and its complexes were characterized by using different techniques including IR, Uv-Vis, 1H and 13C NMR and elemental analysis CHN. According to the abovementioned techniques, a polymeric structure was proposed to the prepared complexes. Further, the structure of Ag(I) complex was confirmed by single crystal X-ray diffraction technique which reveals the polymeric structure trigonal geometry around the Ag+ center. The in vitro antibacterial activity of the prepared ligand and complexes were tested against the standard Escherichia coli (E. coli ATCC 25922), environmental Bacillus sp. and 16 clinical bacterial isolates (both Gram-positive and Gram-negative bacteria) by using amikacin as a standard antibiotic. All the tested compounds except the Zn(II) complex showed antibacterial activities at minimum inhibition concentration (MIC) level, particularly, the silver complex which shows a significant activity with MIC = 15- 250 µg/ml.Keywords: Benzimidazole; Synthesis; Crystal structure; Metal complexes; Antibacterial; Silver.